Young people's perspectives of parent volunteerism in community youth sport. Issue 3 (June 2016) - Trussell, Dawn E.
Highlights: Visible, on-field roles (e.g., coach, announcer) filled by fathers are more highly regarded by young people than their mothers visible, on-field as well as hidden, formal and informal roles (e.g., Board of Directors, fundraiser). Enhanced connection is evident with the parent-volunteer/child-athlete relationship (particularly with on-field roles). Heightened conflict is evident with the parent-volunteer/child-athlete relationship in relation to peer groups as well as siblings. Young people have relatively little understanding of their parents' motivations for volunteering. Abstract: This interpretive study sought to critically examine young people's subjective meanings and experiences related to parent volunteerism in community youth sport. Using a constant comparative method of data analysis, the perspectives of 19 participants from 7 different family units (9 sons and 10 daughters) in Ontario, Canada were examined. The findings call attention to the gendered importance of fathers in highly visible volunteer roles (e.g., coach, game announcer) and the lack of recognition or appreciation for mothers' formal volunteer roles (e.g., assistant coach, league's board of directors) as well as informal volunteer roles (e.g., fundraiser). Moments of conflict in relation to peer groups as well as siblings and the potential for volunteerism to enhance a sense of connection through moments of togetherness and skill development are also emphasized.